Elucidation of the genetic differences in Trialeurodes vaporariorum populations under vegetable greenhouse conditions by using the allozyme approach. Issue 5 (19th August 2013) - Shin, Dongyoung; Mo, Hyoung‐ho; Lee, Sung‐Eun; Park, Jung‐Joon; Cho, Kijong
Abstract Genetic differentiation of Trialeurodes vaporariorum (Westwood 1856) populations was examined using biochemical and allozyme analysis. For biochemical analysis, general esterase and glutathion‐S‐transferase were tested. Allozyme genetic variability in 11 populations of T. vaporariorum was investigated using five loci from four enzyme systems. Although there are large variations between populations, T. vaporariorum is grouped into two populations with geographic barriers, based on Nei's genetic distance in the Baekdudaegan Mountains. Within these two groups, low migration and linkage disequilibrium reveal that populations tend to be influenced by gene drift rather than uniform selection pressures. The effect of genetic drift is greater than the effect of uniform selection by insecticides or host plant resistance, which is suggested by the FST estimates in this study. Based on this basic research, more effective whitefly control programs could be built in the future.